DEGREE OF EXTROVERSION INFLUENCE ON VARIABILITY OF CARDIAC RHYTHM PARAMETERS (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
The subject of the study is the variability of cardiac rhythm parameters, when carrying out a creative assignment, in patients differing in degrees of extroversion. Decreases in the stress index, indicating an increase in the influence of the parasympathetic part of the autonomic nervous system, were identified in introvert subjects. In contrast with introverts, a parasympathetic effect was not observed in extroverted subjects.
Keywords: degree of extraversion, variability in cardiac rhythm, stress index, index of autonomic equilibrium